PERHITUNGAN PENGGUNAAN GENERATOR PADA ALAT TANGKAP BAGAN APUNG DAN KONTRIBUSI TERHADAP EMISI GAS RUMAH KACA - Hairul Umam; Ricky Winrison Fuah; Rosi Rahayu; Afdhal Fuadi; Kurnia Kurnia (JURNAL PERIKANAN TROPIS, 2026)
The Industrial Revolution shifted production toward mechanization, significantly increasing fuel oil (BBM) dependency in Indonesia's fishing sector, particularly for lift net (bagan) operations. Bagan fishermen rely on generators (gensets) to power lamps that attract fish, yet the resulting exhaust emissions threaten environmental quality and climate stability. This study aims to analyze fuel consumption and emissions from gensets used in lift net fishing in Pagatan, South Kalimantan. Using a descriptive quantitative approach, primary data were collected through field observations of lift net units. The results revealed that one Lift net unit consumes approximately 1,000 liters of Pertalite per year, generating 2,300 kg of CO2 emissions annually. Collectively, the 200 units in Pagatan produced 460,000 kg of CO2 per year. These substantial emissions contribute significantly to air pollution and climate change, with CO2 levels reaching 700 ppm potentially impair human cognitive function and physiological health. These findings underscore the urgent need for a transition to eco-friendly alternative energy sources to support government programs in reducing pollution and mitigating climate change impacts in the fisheries sector.keywords: Carbon dioxide; Emissions; Fuel consumption; Generator, Lift net